Composite phase-change electrostatic spinning nanofiber fabric as well as preparation method and application thereof

By preparing nanofiber membranes of MXene and polymers on the surface of composite phase change cotton fabrics, combined with PEG@SiO2 composite phase change material, the problem of composite nanofibers being unable to passively generate heat in low temperature environments is solved, and heat storage and Release, enhances the mechanical properties and stability of the fabric, and is suitable for passive heating needs in sports activities.

CN119287530APending Publication Date: 2025-01-10TONGJI UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411378090.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Existing composite nanofibers cannot passively generate heat and store heat in low temperature environments, and the fiber membrane is too thin to effectively maintain body temperature.

Method used

Electrospinning technology is used to prepare nanofiber membranes on the surface of composite phase change cotton fabrics. A composite formed by MXene and polymer is used to combine PEG@SiO2 composite phase change material to form P-M-PEG@SiO2 composite by impregnation and deposition. Phase change electrospinning nanofiber fabrics realize the storage and release of solar energy converted into thermal energy.

Benefits of technology

Effectively store and release heat, maintain body temperature, enhance mechanical properties and physical stability, reduce phase change material leakage, maintain the softness and moisture permeability of the fabric, and is suitable for passive heating in sports activities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287530A_ABST
    Figure CN119287530A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electrostatic spinning materials, and particularly relates to a composite phase change electrostatic spinning nanofiber fabric and a preparation method and application thereof, and the fabric is obtained by depositing a nanofiber membrane on the surface of a composite phase change cotton fabric through an electrostatic spinning technology; the composite phase change cotton fabric is formed by dipping a cotton fabric in a composite phase change material solution, and the nanofiber membrane is a compound formed by an MXene solution and a high-molecular polymer. Compared with the prior art, the prepared P-M-PEG-coated SiO2 composite phase change nanofiber fabric has the advantages of good photo-thermal conversion performance, heat storage performance and moisture management performance, keeps the mechanical performance advantages of softness, bending resistance, durability and the like of the fabric, fits human skin in practical application and is comfortable, the preparation process is simple, the preparation period is moderate, and the preparation method is suitable for industrial production. The device can be applied to physical education, especially in a low-temperature environment, and passive heating after active warm-up is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrostatic spinning materials, and in particular relates to a composite phase-change electrostatic spinning nanofiber fabric and a preparation method and application thereof. Background Art

[0002] Warm-up exercises are the core content of the preparation part of sports activities. However, the warm-up effect will be lost during the warm-up transition period, especially in low temperature environments. Active warm-up combined with passive heating strategies is crucial to maintain the warm-up effect and improve sports performance: in addition to regular warm-up activities, it is also necessary to wear heating clothing during the subsequent period (warm-up transition period and during exercise) to avoid skin and muscle cooling, which has a positive effect on maintaining the warm-up effect. A demand for heating and thermal insulation fabrics suitable for active warm-up has emerged.

[0003] Electrospinning is a common method for making nanofibers. The thermal comfort and physiological comfort of textiles can be changed by applying a nanofiber layer on the surface of the fabric, making it more breathable, delicate, skin-friendly and soft, and optimizing the wearing experience. MXene has been widely studied in various fields due to its many excellent properties such as large specific surface area, high mechanical strength, good biocompatibility and excellent photothermal performance. As an excellent photothermal conversion material, it has high solar energy capture ability, which is then converted into thermal energy for further use. It is an inexhaustible low-cost clean energy on the earth, so it has become an excellent choice for heating fabric components. At present, CN 116650725A discloses a PVDF / MXene composite nanofiber as a bone tissue engineering scaffold material, which can show a photothermal antibacterial effect under near-infrared laser irradiation. The fiber made by the electrospinning method in this patent has self-heating properties, but the heat loss is fast and cannot store energy, and the fiber membrane layer is too thin to realize the passive heating strategy during the warm-up transition. Summary of the invention

[0004] The purpose of the present invention is to provide a composite phase change electrospinning nanofiber fabric and its preparation method and application in order to solve at least one of the above problems, so as to solve the problem that the composite nanofibers in the prior art cannot passively generate heat and maintain body temperature by storing heat, thereby realizing the effective conversion of solar energy into thermal energy, avoiding leakage of phase change materials in the process, and keeping the fabric soft, bending-resistant and durable.

[0005] The purpose of the present invention is achieved through the following technical solutions:

[0006] One of the technical solutions of the present invention is to provide a composite phase-change electrostatically spun nanofiber fabric, wherein a nanofiber film is prepared on the surface of a composite phase-change cotton fabric by electrostatic spinning technology to obtain the composite phase-change electrostatically spun nanofiber fabric;

[0007] The composite phase change cotton fabric is formed by impregnating cotton fabric in a composite phase change material solution, and the nanofiber membrane is a composite formed by a MXene solution and a high molecular polymer.

[0008] Furthermore, the MXene solution is prepared from a MAX phase material, and the MAX phase material includes one or more of Ti3AlC2, Ti3SiC2, Ti2AlC and Ti3AlCN, preferably Ti3AlC2.

[0009] Furthermore, the high molecular polymer is PVDF-HFP, and the mass fraction is 10%wt-12%wt.

[0010] Furthermore, the composite phase change material solution is prepared by dispersing the phase change material and gas phase silicon dioxide in anhydrous ethanol and stirring at high temperature.

[0011] Furthermore, the preparation process of the composite phase change solution includes: dispersing the phase change material and fumed silica in anhydrous ethanol, and stirring at 60-80° C. at a rate of 200-400 rpm for 20-40 minutes until the solution is clarified and uniform.

[0012] Furthermore, the preparation process of the composite phase change solution is preferably as follows: the phase change material and the fumed silica are dispersed in anhydrous ethanol, and stirred at 70° C. at a rate of 300 rpm for 30 min until the solution is clarified and uniform.

[0013] Furthermore, the phase change material includes one or both of PEG-2000 and PEG-6000, preferably PEG-6000.

[0014] Furthermore, the composite phase change cotton fabric substrate is a PEG@SiO2 composite phase change cotton fabric.

[0015] Furthermore, cotton fabric is immersed in the composite phase change material solution to obtain PEG@SiO2 composite phase change cotton fabric, and the precursor solution is deposited as PVDF / MXene nanofiber membrane on the surface of PEG@SiO2 composite phase change cotton fabric through electrospinning technology to form PM-PEG@SiO2 composite phase change electrospinning nanofiber fabric.

[0016] The second technical solution of the present invention is to provide a method for preparing the composite phase change electrospinning nanofiber fabric as described above, comprising the following steps:

[0017] (1) Processing the MAX phase material to obtain a MXene solution;

[0018] (2) mixing the MXene solution obtained in step (1) with the polymer and stirring them uniformly to obtain an electrospinning precursor solution;

[0019] (3) fully immersing the cotton fabric in the composite phase change material solution and then drying it, repeating this process several times, removing excess composite phase change material on the surface, and obtaining the composite phase change cotton fabric substrate;

[0020] (4) Using the composite phase change cotton fabric substrate prepared in step (3), the electrospinning precursor solution in step (2) is deposited thereon by a deposition method to form a composite phase change electrospinning nanofiber fabric.

[0021] Furthermore, in step (1), the process of treating the MAX phase material includes: chemically etching the MAX phase material, replacing the solvent and centrifuging and concentrating the MAX phase material.

[0022] Furthermore, in step (1), the organic solvent includes one or more of dimethyl sulfoxide (DMSO), dimethyl sulfoxide (DMSO), dimethylformamide (DMF) and acetone, preferably a mixed solution of DMF and acetone.

[0023] Furthermore, in step (2), the stirring time is 10-30 min, preferably 20 min.

[0024] Furthermore, in step (2), the stirring rate is 200-400 rpm, preferably 300 rpm.

[0025] Furthermore, in step (3), the impregnation and drying are both performed under vacuum conditions.

[0026] Furthermore, in step (3), the vacuum degree of the immersion drying is not greater than 1Pa.

[0027] Furthermore, in step (3), the immersion drying temperature is 50-60°C, preferably 55°C.

[0028] Furthermore, in step (3), the immersion drying time is 1-3 hours, preferably 2 hours.

[0029] Furthermore, in step (4), the electrospinning process is carried out on an electrospinning device, the spinning needle specification is 15 inches 21G, the propulsion speed is 1ml / h, the working distance is 15 cm, the working voltage is 15kV, the roller speed is 60r / min, and the deposition is on the fabric surface for 6h.

[0030] The third technical solution of the present invention is to provide a composite phase change electrospun nanofiber fabric as described above in a passive heating garment.

[0031] Further, the passive heating garment is used in physical activities to maintain body temperature after warm-up.

[0032] Compared with the prior art, the present invention has the following advantages:

[0033] 1. The fabric base used for the composite phase change nanofiber fabric of the present invention is a cotton fabric impregnated with a composite phase change material. The phase change material generates heat adsorption by breaking hydrogen bonds when the temperature rises, and re-establishes intramolecular hydrogen bonds when the temperature drops, thereby enhancing the degree of structural order and causing heat release. A large amount of heat can be stored and released. During the preparation process, the composite phase change material is evenly impregnated in the base fabric through repeated impregnation and drying. Compared with fabrics whose base is not impregnated with composite phase change materials, the present invention can effectively convert solar energy into thermal energy, and can store heat for a period of time after the end of illumination, thereby meeting the human body's passive heating needs.

[0034] 2. The fabric substrate used for the composite phase change nanofiber fabric of the present invention is a cotton fabric impregnated with a composite phase change material. The composite phase change material PEG@SiO2 impregnated cotton fabric can enhance its mechanical properties, improve physical stability, and make the fibers more tightly bonded. Weighing found that the impregnation rate of the cotton fabric impregnated with the composite phase change material was about 45%, while the impregnation rate of the cotton fabric PEG@Cotton impregnated only with the phase change material was as high as 650%. Reducing the amount of PEG also helps to reduce the leakage of the phase change material. Compared with the fabric with the base only impregnated with the phase change material, the PM-PEG@SiO2 composite phase change nanofiber fabric prepared by the present invention has no obvious material leakage under high temperature heating conditions and can still maintain good fiber properties.

[0035] 3. The present invention adopts an electrospinning method to deposit PVDF / MXene nanofiber membrane on a composite phase change cotton fabric substrate. The PVDF / MXene nanofiber membrane has the hydrophobic properties of the high molecular polymer PVDF, the good photothermal properties of MXene and the energy storage capacity of the phase change material, and has good photothermal properties and moisture management properties. By using a composite phase change material to reduce the impregnation rate, the original flexibility and moisture permeability are retained. Therefore, the fabric has the advantages of good photothermal conversion performance, heat storage performance and moisture management performance, and maintains the mechanical properties of the fabric such as softness, bending resistance and durability.

[0036] 4. The PM-PEG@SiO2 composite phase change nanofiber fabric prepared by the present invention fits human skin and is comfortable in practical applications. The preparation process is simple and the preparation cycle is moderate. It can be applied to physical education, especially in low temperature environments, to achieve passive heating after active warm-up. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 These are SEM schematic diagrams of the upper and lower surfaces and cross-section of P-M-PEG@SiO2 in Example 1, where a is magnified 20,000 times, b is magnified 100 times, and c is magnified 80 times.

[0038] Figure 2 This is an EDS schematic diagram of P-M-PEG@SiO2 in Example 1.

[0039] Figure 3 This is the actual product of P-M-PEG@SiO2 in Example 1. (1) is the PM-PEG@SiO2 material cut into a size of 6 cm×2 cm; (2) is a schematic diagram of the bending of the PM-PEG@SiO2 material.

[0040] Figure 4 This is the XRD schematic diagram of P-M-PEG@SiO2 in Example 1.

[0041] Figure 5 This is the DSC curve of Example 1 after 5 endothermic and exothermic cycles.

[0042] Figure 6 This is the photothermal conversion and storage curve of P-M-PEG@SiO2 in Example 1.

[0043] Figure 7 This is the photothermal conversion and storage curve of Comparative Example 1.

[0044] Figure 8 This is the photothermal conversion and storage curve of Comparative Example 2.

[0045] Fig. 9 Schematic diagram of the water contact angle of the nanofiber membrane layer of P-M-PEG@SiO2 in Example 1.

[0046] Fig.10 It is a comparison chart of water vapor transmission rate between Example 1 and blank control group.

[0047] Fig.11 Schematic diagram of the leakage of phase change material after heating in Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0048] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0049] Unless otherwise specified, the reagents, methods, instruments and equipment used in the present invention are conventional reagents, methods, instruments and equipment in the art. Unless otherwise specified, the reagents and materials used in the following examples are commercially available and of analytical grade.

[0050] The present invention first provides a composite phase-change electrostatically spun nanofiber fabric, wherein a nanofiber film is prepared on the surface of a composite phase-change cotton fabric by an electrostatic spinning technique to obtain the composite phase-change electrostatically spun nanofiber fabric;

[0051] The composite phase change cotton fabric is formed by impregnating cotton fabric in a composite phase change material solution, and the nanofiber membrane is a composite formed by a MXene solution and a high molecular polymer.

[0052] The MXene solution is prepared from MAX phase material, and the MAX phase material includes one or more of Ti3AlC2, Ti3SiC2, Ti2AlC and Ti3AlCN, preferably Ti3AlC2; the high molecular polymer is PVDF-HFP, with a mass fraction of 10%wt-12%wt.

[0053] The composite phase change material solution is prepared by dispersing the phase change material and the fumed silica in anhydrous ethanol and stirring under high temperature conditions. The preparation process includes: dispersing the phase change material and the fumed silica in anhydrous ethanol, and stirring at a rate of 200-400rpm for 20-40min at 60-80°C until the solution is clarified and uniform; preferably: dispersing the phase change material and the fumed silica in anhydrous ethanol, and stirring at a rate of 300rpm for 30min at 70°C until the solution is clarified and uniform.

[0054] The phase change material includes one or both of PEG-2000 and PEG-6000, preferably PEG-6000.

[0055] The composite phase change cotton fabric substrate is a PEG@SiO2 composite phase change cotton fabric.

[0056] Cotton fabric is immersed in the composite phase change material solution to obtain PEG@SiO2 composite phase change cotton fabric. The precursor solution is deposited as PVDF / MXene nanofiber membrane on the surface of PEG@SiO2 composite phase change cotton fabric through electrospinning technology to form PM-PEG@SiO2 composite phase change electrospinning nanofiber fabric.

[0057] The present invention also provides a method for preparing the composite phase change electrospinning nanofiber fabric as described above, comprising the following steps:

[0058] (1) Preparation of MXene organic solution: chemical etching, solvent replacement and centrifugal concentration of the MAX phase material to obtain a MXene solution dissolved in an organic solvent with a suitable concentration;

[0059] (2) Preparation of electrospinning precursor solution: The MXene solution prepared in step (1) is mixed and stirred with the high molecular weight polymer PVDF-HFP to obtain an electrospinning precursor solution, which is prepared for the electrospinning step;

[0060] (3) Preparation of composite phase change cotton fabric: The phase change material and fumed silica are stirred in anhydrous ethanol until uniform, and the pure cotton non-woven fabric is fully impregnated with the composite phase change material solution under a vacuum environment, and the solvent is removed by vacuum drying, and the steps are repeated, and the excess composite phase change material on the surface is washed with ethanol to obtain PEG@SiO2 composite phase change cotton fabric;

[0061] (4) Preparation of composite phase change electrospun nanofiber fabric: Using the composite phase change cotton fabric substrate prepared in step (3), the electrospinning precursor solution in step (2) is deposited thereon by a deposition method to form a composite phase change electrospun nanofiber fabric.

[0062] In step (1), the organic solvent includes one or more of dimethyl sulfoxide (DMSO), dimethyl sulfoxide (DMSO), dimethylformamide (DMF) and acetone, preferably a mixed solution of DMF and acetone.

[0063] In step (2), the stirring time is 10-30 min, preferably 20 min; the stirring rate is 200-400 rpm, preferably 300 rpm.

[0064] The impregnation and drying are both carried out under vacuum conditions; the vacuum degree of the impregnation and drying is not greater than 1 Pa; the temperature of the impregnation and drying is 50-60° C., preferably 55° C.; the time of the impregnation and drying is 1-3 hours, preferably 2 hours.

[0065] The present invention also provides an application of the composite phase change electrospun nanofiber fabric as described above in passive heating clothing, especially in sports activities.

[0066] See next Figure 1-Figure 11 , the implementation modes of the present invention are described in detail.

[0067] Example 1

[0068] (1) Preparation of MXene organic solution: 5 mL of deionized water, 15 mL of HCL, 1.6 g of LiF, and 1.0 g of Ti3AlC2 were weighed for etching reaction and stirred continuously at 35 °C for 24 h. The mixture was then centrifuged at 3500 rpm for 40 min to obtain a swollen multilayer clay-like MXene precipitate, which then replaced the solvent DMF. After ultrasonic treatment for 80 min, the collected supernatant was finally concentrated by centrifugation at 10000 rpm for 10 min to obtain Ti3C2T x Organic solution of MXene (sampling concentration is 10 mg / mL).

[0069] (2) Preparation of electrospinning precursor solution: 4.5 mL of the above MXene organic solution, 0.5 mL of acetone, and 0.6 g of PVDF-HFP were mixed and stirred at 300 rpm for 20 min.

[0070] (3) Preparation of composite phase change cotton fabric: First, PEG-6000 (85% wt) and fumed silica were dispersed in anhydrous ethanol and stirred at 300 rpm at 70°C until clear and transparent. Then, the non-woven cotton fabric was immersed in the solution and placed in a vacuum oven at 55°C under high vacuum (<1Pa) for 2 h. After being taken out, the steps were repeated. Finally, the excess composite phase change material on the surface was washed off with ethanol and then dried. A uniformly impregnated PEG@SiO2 composite phase change cotton fabric was successfully obtained.

[0071] (4) Preparation of composite phase-change nanofiber fabric: The PEG@SiO2 composite phase-change cotton fabric in step (3) is used as the receiving substrate, the electrospinning precursor solution obtained in step (2) is electrospun into a nanofiber membrane, and a composite phase-change nanofiber fabric (PM-PEG@SiO2) is obtained by a deposition method. The spinning needle specification is 15 inches 21G, the propulsion speed is 1ml / h, the working distance is 15 cm, the working voltage is 15kV, the roller speed is 60r / min, and it is deposited on the fabric surface.

[0072] Example 2

[0073] (1) Preparation of MXene organic solution: 5 mL of deionized water, 15 mL of HCL, 1.6 g of LiF, and 1.0 g of Ti3AlC2 were weighed for etching reaction and stirred continuously at 35 °C for 24 h. The mixture was then centrifuged at 3500 rpm for 40 min to obtain a swollen multilayer clay-like MXene precipitate, which then replaced the solvent DMF. After ultrasonic treatment for 80 min, the collected supernatant was finally concentrated by centrifugation at 10000 rpm for 10 min to obtain Ti3C2T x Organic solution of MXene (sampling concentration is 10 mg / mL).

[0074] (2) Preparation of electrospinning precursor solution: 4.5 mL of the above MXene organic solution, 0.5 mL of acetone, and 0.6 g of PVDF-HFP were mixed and stirred at 300 rpm for 20 min.

[0075] (3) Preparation of composite phase change cotton fabric: First, PEG-2000 (85% wt) and fumed silica were dispersed in anhydrous ethanol and stirred at 300 rpm at 70°C until clear and transparent. Then, the non-woven cotton fabric was immersed in the solution and placed in a vacuum oven at 55°C under high vacuum conditions (<1Pa) for 2 h. After being taken out, the steps were repeated. Finally, the excess composite phase change material on the surface was washed off with ethanol and then dried. A uniformly impregnated PEG@SiO2 composite phase change cotton fabric was successfully obtained.

[0076] (4) Preparation of composite phase-change nanofiber fabric: The PEG@SiO2 composite phase-change cotton fabric in step (3) is used as the receiving substrate, the electrospinning precursor solution obtained in step (2) is electrospun into a nanofiber membrane, and a composite phase-change nanofiber fabric (PM-PEG@SiO2) is obtained by a deposition method. The spinning needle specification is 15 inches 21G, the propulsion speed is 1ml / h, the working distance is 15 cm, the working voltage is 15kV, the roller speed is 60r / min, and it is deposited on the fabric surface.

[0077] Example 3

[0078] (1) Preparation of MXene organic solution: 5 mL of deionized water, 15 mL of HCL, 1.6 g of LiF, and 1.0 g of Ti3AlC2 were weighed for etching reaction and stirred continuously at 35 °C for 24 h. The mixture was then centrifuged at 3500 rpm for 40 min to obtain a swollen multilayer clay-like MXene precipitate, which then replaced the solvent DMF. After ultrasonic treatment for 80 min, the collected supernatant was finally concentrated by centrifugation at 10000 rpm for 10 min to obtain Ti3C2T x Organic solution of MXene (sampling concentration is 10 mg / mL).

[0079] (2) Preparation of electrospinning precursor solution: 4.5 mL of the above MXene organic solution, 0.5 mL of acetone, and 0.6 g of PVDF-HFP were mixed and stirred at 300 rpm for 20 min.

[0080] (3) Preparation of composite phase change cotton fabric: First, PEG-6000 (85% wt) and fumed silica were dispersed in anhydrous ethanol and stirred at 25,000 rpm at 80°C until clear and transparent. Then, the non-woven cotton fabric was immersed in the solution and placed in a vacuum oven at 55°C under high vacuum conditions (<1Pa) for 2 h. After being taken out, the steps were repeated. Finally, the excess composite phase change material on the surface was washed off with ethanol and then dried. A uniformly impregnated PEG@SiO2 composite phase change cotton fabric was successfully obtained.

[0081] (4) Preparation of composite phase-change nanofiber fabric: The PEG@SiO2 composite phase-change cotton fabric in step (3) is used as the receiving substrate, the electrospinning precursor solution obtained in step (2) is electrospun into a nanofiber membrane, and a composite phase-change nanofiber fabric (PM-PEG@SiO2) is obtained by a deposition method. The spinning needle specification is 15 inches 21G, the propulsion speed is 1ml / h, the working distance is 15 cm, the working voltage is 15kV, the roller speed is 60r / min, and it is deposited on the fabric surface.

[0082] Example 4

[0083] (1) Preparation of MXene organic solution: 5 mL of deionized water, 15 mL of HCL, 1.6 g of LiF, and 1.0 g of Ti2AlC were weighed for etching reaction and stirred continuously at 35 °C for 24 h. The mixture was then centrifuged at 3500 rpm for 40 min to obtain a swollen multilayer clay-like MXene precipitate, which then replaced the solvent DMF. After ultrasonic treatment for 80 min, the collected supernatant was finally centrifuged at 10000 rpm for 10 min to obtain Ti2CT. x Organic solution of MXene (sampling concentration is 10 mg / mL).

[0084] (2) Preparation of electrospinning precursor solution: 4.5 mL of the above MXene organic solution, 0.5 mL of acetone, and 0.6 g of PVDF-HFP were mixed and stirred at 300 rpm for 20 min.

[0085] (3) Preparation of composite phase change cotton fabric: First, PEG-6000 (85% wt) and fumed silica were dispersed in anhydrous ethanol and stirred at 300 rpm at 70°C until clear and transparent. Then, the non-woven cotton fabric was immersed in the solution and placed in a vacuum oven at 55°C under high vacuum (<1Pa) for 2 h. After being taken out, the steps were repeated. Finally, the excess composite phase change material on the surface was washed off with ethanol and then dried. A uniformly impregnated PEG@SiO2 composite phase change cotton fabric was successfully obtained.

[0086] (4) Preparation of composite phase-change nanofiber fabric: The PEG@SiO2 composite phase-change cotton fabric in step (3) is used as the receiving substrate, the electrospinning precursor solution obtained in step (2) is electrospun into a nanofiber membrane, and a composite phase-change nanofiber fabric (PM-PEG@SiO2) is obtained by a deposition method. The spinning needle specification is 15 inches 21G, the propulsion speed is 1ml / h, the working distance is 15 cm, the working voltage is 15kV, the roller speed is 60r / min, and it is deposited on the fabric surface.

[0087] Example 5

[0088] (1) Preparation of MXene organic solution: 5 mL of deionized water, 15 mL of HCL, 1.6 g of LiF, and 1.0 g of Ti3AlC2 were weighed for etching reaction and stirred continuously at 35 °C for 24 h. The mixture was then centrifuged at 3500 rpm for 40 min to obtain a swollen multilayer clay-like MXene precipitate, after which the solvent DMSO was replaced. After ultrasonic treatment for 80 min, the collected supernatant was finally concentrated by centrifugation at 10000 rpm for 10 min to obtain Ti3C2T x Organic solution of MXene (sampling concentration is 10 mg / mL).

[0089] (2) Preparation of electrospinning precursor solution: 4.5 mL of the above MXene organic solution, 0.5 mL of acetone, and 0.6 g of PVDF-HFP were mixed and stirred at 300 rpm for 20 min.

[0090] (3) Preparation of composite phase change cotton fabric: First, PEG-6000 (85% wt) and fumed silica were dispersed in anhydrous ethanol and stirred at 300 rpm at 70°C until clear and transparent. Then, the non-woven cotton fabric was immersed in the solution and placed in a vacuum oven at 55°C under high vacuum (<1Pa) for 2 h. After being taken out, the steps were repeated. Finally, the excess composite phase change material on the surface was washed off with ethanol and then dried. A uniformly impregnated PEG@SiO2 composite phase change cotton fabric was successfully obtained.

[0091] (4) Preparation of composite phase-change nanofiber fabric: The PEG@SiO2 composite phase-change cotton fabric in step (3) is used as the receiving substrate, the electrospinning precursor solution obtained in step (2) is electrospun into a nanofiber membrane, and a composite phase-change nanofiber fabric (PM-PEG@SiO2) is obtained by a deposition method. The spinning needle specification is 15 inches 21G, the propulsion speed is 1ml / h, the working distance is 15 cm, the working voltage is 15kV, the roller speed is 60r / min, and it is deposited on the fabric surface.

[0092] Example 6

[0093] (1) Preparation of MXene organic solution: 5 mL of deionized water, 15 mL of HCL, 1.6 g of LiF, and 1.0 g of Ti3AlC2 were weighed for etching reaction and stirred continuously at 35 °C for 24 h. The mixture was then centrifuged at 3500 rpm for 40 min to obtain a swollen multilayer clay-like MXene precipitate, which then replaced the solvent DMF. After ultrasonic treatment for 80 min, the collected supernatant was finally concentrated by centrifugation at 10000 rpm for 10 min to obtain Ti3C2T x Organic solution of MXene (sampling concentration is 10 mg / mL).

[0094] (2) Preparation of electrospinning precursor solution: 4.5 mL of the above MXene organic solution, 0.5 mL of acetone, and 0.6 g of PVDF-HFP were mixed and stirred at 200 rpm for 30 min.

[0095] (3) Preparation of composite phase change cotton fabric: First, PEG-6000 (85% wt) and fumed silica were dispersed in anhydrous ethanol and stirred at 300 rpm at 70°C until clear and transparent. Then, the non-woven cotton fabric was immersed in the solution and placed in a vacuum oven at 55°C under high vacuum (<1Pa) for 2 h. After being taken out, the steps were repeated. Finally, the excess composite phase change material on the surface was washed off with ethanol and then dried. A uniformly impregnated PEG@SiO2 composite phase change cotton fabric was successfully obtained.

[0096] (4) Preparation of composite phase-change nanofiber fabric: The PEG@SiO2 composite phase-change cotton fabric in step (3) was used as the receiving substrate, and the electrospinning precursor solution obtained in step (2) was electrospun into a nanofiber membrane, and a composite phase-change nanofiber fabric (PM-PEG@SiO2) was obtained by a deposition method. The spinning needle specification was 15 inches 21G, the propulsion speed was 1ml / h, the working distance was 15 cm, the working voltage was 15kV, the roller speed was 60r / min, and it was deposited on the fabric surface.

[0097] Example 7

[0098] (1) Preparation of MXene organic solution: 5 mL of deionized water, 15 mL of HCL, 1.6 g of LiF, and 1.0 g of Ti3AlC2 were weighed for etching reaction and stirred continuously at 35 °C for 24 h. The mixture was then centrifuged at 3500 rpm for 40 min to obtain a swollen multilayer clay-like MXene precipitate, which then replaced the solvent DMF. After ultrasonic treatment for 80 min, the collected supernatant was finally concentrated by centrifugation at 10000 rpm for 10 min to obtain Ti3C2T x Organic solution of MXene (sampling concentration is 10 mg / mL).

[0099] (2) Preparation of electrospinning precursor solution: 4.5 mL of the above MXene organic solution, 0.5 mL of acetone, and 0.6 g of PVDF-HFP were mixed and stirred at 300 rpm for 20 min.

[0100] (3) Preparation of composite phase change cotton fabric: First, PEG-6000 (85% wt) and fumed silica were dispersed in anhydrous ethanol and stirred at 300 rpm at 70°C until clear and transparent. Then, the non-woven cotton fabric was immersed in the solution and placed in a vacuum oven at 60°C under high vacuum conditions (<1Pa) for 1.5 h. After being taken out, the steps were repeated. Finally, the excess composite phase change material on the surface was washed off with ethanol and then dried. A uniformly impregnated PEG@SiO2 composite phase change cotton fabric was successfully obtained.

[0101] (4) Preparation of composite phase-change nanofiber fabric: The PEG@SiO2 composite phase-change cotton fabric in step (3) was used as the receiving substrate, and the electrospinning precursor solution obtained in step (2) was electrospun into a nanofiber membrane, and a composite phase-change nanofiber fabric (PM-PEG@SiO2) was obtained by a deposition method. The spinning needle specification was 15 inches 21G, the propulsion speed was 1ml / h, the working distance was 15 cm, the working voltage was 15kV, the roller speed was 60r / min, and it was deposited on the fabric surface.

[0102] Comparative Example 1:

[0103] This comparative example provides a phase change nanofiber fabric impregnated with only pure phase change material.

[0104] (1) Preparation of MXene organic solution: 5 mL of deionized water, 15 mL of HCL, 1.6 g of LiF, and 1.0 g of Ti3AlC2 were weighed for etching reaction and stirred continuously at 35 °C for 24 h. The mixture was then centrifuged at 3500 rpm for 40 min to obtain a swelling precipitate and then replace the solvent DMF. After ultrasonic treatment for 80 min, the collected supernatant was finally concentrated by centrifugation at 10000 rpm for 10 min to obtain Ti3C2T x Organic solution of MXene (sampling concentration is 10 mg / mL).

[0105] (2) Preparation of electrospinning precursor solution: 4.5 mL of the above MXene organic solution, 0.5 mL of acetone, and 0.6 g of PVDF-HFP were mixed and stirred at 300 rpm for 20 min.

[0106] (3) Preparation of phase change cotton fabric: First, PEG-6000 was placed in a water bath at 70°C until it was clear and transparent. Then, the non-woven cotton fabric was immersed in the PEG-6000 solution and placed in a vacuum oven at 85°C under high vacuum conditions (<1Pa) for 1 hour. After being taken out, it was placed on filter paper and continued to be dried in a vacuum oven for 3 hours. The cotton fabric impregnated with pure phase change material (PEG@Cotton) was successfully obtained.

[0107] (4) Preparation of phase change nanofiber fabric: Using the PEG@Cotton phase change cotton fabric in step (3) as the receiving substrate, the electrospinning precursor solution obtained in step (2) was electrospun into a nanofiber membrane, and a composite phase change nanofiber fabric (PM-PEG@Cotton) was obtained by deposition. The spinning needle specification was 15 inches 21G, the propulsion speed was 1ml / h, the working distance was 15 cm, the working voltage was 15kV, the roller speed was 60r / min, and it was deposited on the fabric surface.

[0108] Comparative Example 2:

[0109] This comparative example provides a nanofiber fabric without adding a phase change material.

[0110] (1) Preparation of MXene organic solution: 5 mL of deionized water, 15 mL of HCL, 1.6 g of LiF, and 1.0 g of Ti3AlC2 were weighed for etching reaction and stirred continuously at 35 °C for 24 h. The mixture was then centrifuged at 3500 rpm for 40 min to obtain a swelling precipitate and then replace the solvent DMF. After ultrasonic treatment for 80 min, the collected supernatant was finally concentrated by centrifugation at 10000 rpm for 10 min to obtain Ti3C2T x Organic solution of MXene (sampling concentration is 10 mg / mL).

[0111] (2) Preparation of electrospinning precursor solution: 4.5 mL of the above MXene organic solution, 0.5 mL of acetone, and 0.6 g of PVDF-HFP were mixed and stirred at 300 rpm for 20 min.

[0112] (3) Preparation of nanofiber fabric: The non-woven cotton fabric after plasma treatment was used as the receiving substrate, and the electrospinning precursor solution obtained in step (2) was electrospun into a nanofiber membrane, and the nanofiber fabric (PM-Cotton) was obtained by deposition. The spinning needle specification was 15 inches 21G, the propulsion speed was 1ml / h, the working distance was 15 cm, the working voltage was 15kV, the roller speed was 60r / min, and it was deposited on the fabric surface.

[0113] Then, Example 1 and Comparative Examples 1-2 were tested as follows:

[0114] (1) Surface morphology characterization: The upper and lower surfaces of the composite phase change nanofiber fabric (PM-PEG@SiO2) of Example 1 were characterized by scanning electron microscopy (SEM):

[0115] like Figure 1 As shown, Figure 1The SEM schematic diagram of the upper and lower surfaces and cross-section of P-M-PEG@SiO2 in Example 1 under a scanning electron microscope magnified 20,000 times, 100 times and 80 times. From the SEM images of the upper and lower surfaces of PM-PEG@SiO2, it can be seen that the present invention successfully uses electrospinning and vacuum drying methods to prepare the photothermal layer and the phase change layer; the SEM image of the cross-section shows that the prepared PVDF / MXene nanofiber membrane is well bonded to the base layer PEG@SiO2 composite phase change cotton fabric.

[0116] (2) Elemental analysis: The composite phase change nanofiber fabric (PM-PEG@SiO2) of Example 1 was subjected to elemental analysis using an X-ray spectrometer:

[0117] like Figure 2 As shown, Figure 2 The front EDS image of PM-PEG@SiO2 shows that the main components of the nanofiber membrane layer are C, F, and Ti, indicating that PVDF and MXene materials were successfully composited by electrospinning; the back EDS image shows that the main components of the composite phase change cotton fabric layer are C, O, and Si, and the fluorescence distribution is uniform, indicating that the composite phase change material is evenly impregnated on the non-woven cotton fabric.

[0118] (3) Bending capacity analysis: Figure 3 As shown, Figure 3 This is the actual composite phase change nanofiber fabric (PM-PEG@SiO2) of the present invention. (1) is cut into a size of 6cm×2cm; (2) is a schematic diagram of the bending of a 6cm×2cm material. It can be seen that the PM-PEG@SiO2 composite phase change nanofiber fabric has good bending ability.

[0119] (4) Material composition characterization: The composite phase change nanofiber fabric (PM-PEG@SiO2) of Example 1 was analyzed using an X-ray diffractometer:

[0120] like Figure 4 As shown, Figure 4 The XRD diagram shows the structure of the PM-PEG@SiO2 composite phase change nanofiber fabric prepared by the present invention. The MXene peak is located at the lowest 2θ angle, indicating the existence of a layered structure, proving that the MXene was successfully prepared; the X-ray diffraction pattern of SiO2 is shown near 2θ=22.8°; many characteristic peaks of PEG are observed at 2θ=14.7°, 16.5°, and 19.1°.

[0121] (5) Thermal performance test: The thermal performance test of Example 1 was carried out 5 times using differential scanning calorimetry (DSC):

[0122] Figure 5The DSC curve shows that after PM-PEG@SiO2 has undergone 5 endothermic and exothermic cycles, except for the first time when the melting enthalpy is slightly higher, the curves under the cyclic conditions are highly overlapped. This indicates that the PM-PEG@SiO2 composite phase change nanofiber fabric of the present invention maintains stable chemical properties under the endothermic and exothermic cycle. This is because the composite phase change material PEG@SiO2 has chemical stability and low leakage capacity. Therefore, the PM-PEG@SiO2 composite phase change nanofiber fabric of the present invention can meet the needs of recycling under the passive heating strategy of the human body.

[0123] (6) Photothermal conversion test: Under a xenon lamp simulating a light source with the intensity of sunlight, the photothermal conversion capacity of Example 1 under one illumination cycle was recorded using an infrared thermal imager:

[0124] like Figure 6-Figure 8 As shown, Figure 6 The photothermal conversion and storage curves show that the PM-PEG@SiO2 composite phase change nanofiber fabric can be effectively converted into thermal energy under the irradiation of xenon lamps to simulate sunlight, and the introduction of phase change materials can effectively slow down the heat loss after the loss of light conditions. The energy storage effect of the phase change material forms a 40-44°C temperature platform between the end of the light, which can meet the needs of passive heating of the human body. Figure 7 The curve of comparative example 1 has the same effect, but a larger mass fraction will also cause the melting endothermic process of the phase change material to slow down and the heating time to be longer. Figure 8 The temperature of Comparative Example 2 dropped significantly after the illumination ended, indicating that Comparative Example 2 did not have an energy storage effect and was not conducive to meeting the passive heating needs of the human body.

[0125] (7) Hydrophobicity test: The water contact angle of Example 1 was measured, and the hydrophobicity test of the PM-PEG@SiO2 composite phase change nanofiber fabric was performed:

[0126] Fig. 9 The water contact angle of the nanofiber layer is 142°, indicating that the front side of the PM-PEG@SiO2 composite phase change nanofiber fabric of the present invention has good hydrophobic properties. Since PVDF itself has low surface energy, the water contact angle is about 110°. After the nanofibers are formed by electrospinning technology, the surface roughness, holes, gaps between fibers and other structures increase the clamping of air between the fiber surface and water molecules, so it has higher water repellency. In addition to the passive heating function for the human body, it also has a sweating effect.

[0127] (8) Water vapor transmission rate test: The water vapor transmission performance of the covered sample of Example 1 and the blank control (without covering) was measured at 37°C:

[0128] Fig.10The water vapor permeability bar graph shows that compared with the blank control (no covering), the PM-PEG@SiO2 composite phase change nanofiber fabric has good water vapor permeability under 37°C environmental conditions. This is due to the characteristics of the composite phase change nanofiber fabric, such as the light impregnation rate of the fabric substrate, the many pores between nanofibers, the low fiber density, and the large surface area, which allows water vapor to pass through this film smoothly.

[0129] (9) Phase change material leakage test: Under the heating condition of 70° C. on a heating table, the leakage of the phase change materials of Example 1 and Comparative Example 1 that were absorbed by filter paper was tested for leakage degree:

[0130] like Fig.11 As shown, the PEG@Cotton of comparative example 1 leaked obviously after being heated on a heating table at 70°C, while there was no leakage in example 1 under the same conditions, indicating that the composite phase change material was successfully prepared and the leakage of the phase change material was avoided. The reason is that the cotton fabric with the addition of the composite phase change material PEG@SiO2 can enhance the mechanical properties, improve the physical stability, and make the bonding between the fibers tighter. Weighing found that the impregnation rate of the cotton fabric impregnated with the composite phase change material was about 45%, while the impregnation rate of the cotton fabric PEG@Cotton impregnated only with the phase change material was as high as 650%. Reducing the amount of PEG can also help reduce the leakage of the phase change material.

[0131] In summary, the PM-PEG@SiO2 composite phase change nanofiber fabric of the present invention can not only perform photothermal conversion and phase change energy storage through solar energy to meet the needs of passive heating when actually used, but also has good moisture management performance, hydrophobicity and high water vapor permeability. The present invention combines functionality and thermal comfort performance, meeting the implementation of passive heating strategies during the transition period after warm-up in physical education and during exercise.

[0132] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A composite phase change electrospun nanofiber fabric, characterized in that: The composite phase-change electrostatically spun nanofiber fabric is prepared by using an electrostatic spinning technique on the surface of the composite phase-change cotton fabric to obtain the composite phase-change electrostatically spun nanofiber fabric; The composite phase change cotton fabric is formed by impregnating cotton fabric in a composite phase change material solution, and the nanofiber membrane is a composite formed by a MXene solution and a high molecular polymer.

2. The composite phase change electrospun nanofiber fabric according to claim 1, characterized in that: The MXene solution is prepared from a MAX phase material, and the MAX phase material includes one or more of Ti3AlC2, Ti3SiC2, Ti2AlC and Ti3AlCN.

3. The composite phase change electrospun nanofiber fabric according to claim 1, characterized in that: The high molecular polymer is PVDF-HFP.

4. The composite phase change electrospun nanofiber fabric according to claim 1, characterized in that: The composite phase change material solution is prepared by dispersing phase change material and gas phase silicon dioxide in anhydrous ethanol and stirring under high temperature conditions.

5. The composite phase change electrospun nanofiber fabric according to claim 4, characterized in that: The phase change material includes one or both of PEG-2000 and PEG-6000.

6. The composite phase change electrospun nanofiber fabric according to claim 1, characterized in that: Cotton fabric is immersed in the composite phase change material solution to obtain PEG@SiO2 composite phase change cotton fabric. The precursor solution is deposited as PVDF / MXene nanofiber membrane on the surface of PEG@SiO2 composite phase change cotton fabric through electrospinning technology to form PM-PEG@SiO2 composite phase change electrospinning nanofiber fabric.

7. A method for preparing the composite phase change electrospun nanofiber fabric as claimed in claim 1, characterized in that: The following steps are involved: (1) Processing the MAX phase material to obtain a MXene solution; (2) mixing the MXene solution obtained in step (1) with the polymer and stirring them uniformly to obtain an electrospinning precursor solution; (3) fully immersing the cotton fabric in the composite phase change material solution and then drying it, repeating this process several times, removing excess composite phase change material on the surface, and obtaining the composite phase change cotton fabric substrate; (4) Using the composite phase change cotton fabric substrate prepared in step (3), the electrospinning precursor solution in step (2) is deposited thereon by a deposition method to form a composite phase change electrospinning nanofiber fabric.

8. The method for preparing a composite phase-change electrospinning nanofiber fabric according to claim 7, characterized in that: In step (3), the impregnation and drying are both carried out under vacuum conditions.

9. The method for preparing a composite phase-change electrospinning nanofiber fabric according to claim 7, characterized in that: The electrospinning process is carried out on an electrospinning device, with a spinning needle specification of 15 inches 21G, a propulsion speed of 1 ml / h, a working distance of 15 cm, a working voltage of 15 kV, a roller speed of 60 r / min, and deposition on the fabric surface for 6 hours.

10. Use of the composite phase-change electrospun nanofiber fabric as claimed in claim 1 in passive heating clothing.

Citation Information

Patent Citations

  • Preparation method of polyethylene glycol / silicon dioxide composite phase change energy storage material

    CN106811179A

  • Preparation method and application of electrospun PVDF (Polyvinylidene Fluoride) fiber membrane with excellent thermal conductivity and hydrophilicity

    CN114164646A

  • Photo-thermal self-pumping fabric and preparation method thereof

    CN115195221A

  • Photoinduced heating and temperature sensing elastic phase change energy storage fiber and preparation method thereof

    CN116590915A

  • Nanofiber Non-Woven Composite

    US20120076972A1